Workload stress and conservatism: An audit perspective - Novrys Suhardianto; Sidney C. M. Leung (Cogent Business & Management, 2020)
Current literature on audit workload stress suggests that the pressure may adversely affect audit quality. However, compromised audit quality would attract regulatory enforcement and costly reputation loss. Therefore, it is crucial to explore the association between audit workload and audit conservatism as a mechanism to mitigate audit risks. Using a new audit engagement database provided by PCAOB to measure the workload at the partner level, this study argues that the probability of issuing modified audit opinion and going concern opinion is predicted to increase as the audit workload escalates conditional on the ability to manage the workload. The findings show that audit workload induces over-conservatism as it increases the probability of modifying audit opinion and committing a type I error by reducing the accuracy of going concern opinion. This study also demonstrates that the workload effect is less severe for audit firms with sufficient resources and industry-specific knowledge that necessary to manage the workload effectively. This study examines the determinants of audit conservatism from the auditor side, while current literature focuses more on the client's characteristics. This study sheds light on the importance of the audit resources to mitigate the stress effect. However, this study is unable to observe the number of non-listed audit clients of audit firms due to the limitations of audit engagement database.
Keywords: 650; audit conservatism; auditor workload stress; modified audit opinion; going concern opinion